A NEW DIAGNOSTIC APPROACH TO HLA TESTING IN KIDNEY TRANSPLANT RECIPIENTS USING CULTURED URINE DERIVED TUBULAR CELLS - Spriewald, Bernd; Herrmann, Markus; Bach, Christian; Knaup, Karl; Krumbiegel, Mandy; Wiesmann da Silva Reis, André; Schiffer, Mario; Wiesener, Michael (Joint 34th European Immunogenetics and Histocompatibility and 31st British Society for Histocompatibility and Immunogenetics Conference, 2020)
CRIS-Team WoS Importer:2020-03-24

An intermediate-effect size variant in UMOD confers risk for chronic kidney disease - Olinger, Eric; Schaeffer, Céline; Kidd, Kendrah; Elhassan, Elhussein A.E.; Cheng, Yurong; Dufour, Inès; Schiano, Guglielmo; Mabillard, Holly; Pasqualetto, Elena; Hofmann, Patrick; Fuster, Daniel G.; Kistler, Andreas D.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2022)
The kidney-specific gene UMOD encodes for uromodulin, the most abundant protein excreted in normal urine. Rare large-effect variants in UMOD cause autosomal dominant tubulointerstitial kidney disease (ADTKD), while common low-impact variants strongly associate with kidney function and the risk of chronic kidney disease (CKD) in the general population. It is unknown whether intermediate-effect variants in UMOD contribute to CKD. Here, candidate intermediate-effect UMOD variants were identified using large-population and ADTKD cohorts. Biological and phenotypical effects were investigated using cell models, in silico simulations, patient samples, and international databases and biobanks. Eight UMOD missense variants reported in ADTKD are present in the Genome Aggregation Database (gnomAD), with minor allele frequency (MAF) ranging from 1025 to 1023. Among them, the missense variant p.Thr62Pro is detected in ∼1/1,000 individuals of European ancestry, shows incomplete penetrance but a high genetic load in familial clusters of CKD, and is associated with kidney failure in the 100,000 Genomes Project (odds ratio [OR] = 3.99 [1.84 to 8.98]) and the UK Biobank (OR = 4.12 [1.32 to 12.85). Compared with canonical ADTKD mutations, the p.Thr62Pro carriers displayed reduced disease severity, with slower progression of CKD and an intermediate reduction of urinary uromodulin levels, in line with an intermediate trafficking defect in vitro and modest induction of endoplasmic reticulum (ER) stress. Identification of an intermediate-effect UMOD variant completes the spectrum of UMOD-associated kidney diseases and provides insights into the mechanisms of ADTKD and the genetic architecture of CKD.
CRIS-Team Scopus Importer:2022-09-02
Keywords: Autosomal Dominant Tubulointerstitial Kidney Disease; ER stress; genetic architecture; rare disease; uromodulin

A noninvasive diagnostic approach to retrospective donor HLA typing in kidney transplant patients using urine - Bach, Christian; Knaup, Karl; Herrmann, Markus; Krumbiegel, Mandy; Pfister, Frederick; Büttner-Herold, Maike; Steffen, Martin; Zecher, Daniel; Lopau, Kai; Schneider, Karen; Dieterle, Anne; Amann, Kerstin Ute; et al. (Transplant International, 2021)
Antibody-mediated rejection (AMR) is a major obstacle to long-term kidney transplantation. AMR is mostly caused by donor specific HLA antibodies, which can arise before or any time after transplantation. Incomplete donor HLA typing and unavailability of donor DNA regularly preclude the assessment of donor-specificity of circulating anti-HLA antibodies. In our centre, this problem arises in approximately 20% of all post-transplant HLA-antibody assessments. We demonstrate that this diagnostic challenge can be resolved by establishing donor renal tubular cell cultures from recipient´s urine as a source of high-quality donor DNA. DNA was then verified for genetic origin and purity by fluorescence in situ hybridization and short tandem repeat analysis. Two representative cases highlight the diagnostic value of this approach which is corroborated by analysis of ten additional patients. The latter were randomly sampled from routine clinical care patients with available donor DNA as controls. In all 12 cases, we were able to perform full HLA typing of the respective donors confirmed by cross-comparison to results from the stored 10 donor DNAs. We propose that this noninvasive diagnostic approach for HLA typing in kidney transplant patients is valuable to determine donor specificity of HLA antibodies, which is important in clinical assessment of suspected AMR.
CRIS-Team Scopus Importer:2021-06-25
Keywords: antibody-mediated rejection; HLA typing; HLA-antibody post-transplantation; rejection

Association of a coding polymorphism in Fc gamma receptor 2A and graft survival in re-transplant candidates - Fuernrohr, Barbara G.; Weiss, Katrin M.; Harre, Ulrike; Wiesener, Michael; Spriewald, Bernd M.; Arnold, Martin (Human Immunology, 2015)
The family of Fc gamma receptors (Fc?Rs) is involved in mediating immunological effector functions. Fc?Rs are differentially expressed on immune cells and can act either activating or inhibitory, with Fc?R2A belonging to the first group. The polymorphism H131R (rs1801274) in FCGR2A has been associated with acute rejection and can shift the overall balance between activating and inhibitory Fc?Rs. Anti-HLA allo-antibodies in transplant recipients have been identified as risk factor for organ survival after transplantation. In this study we genotyped FCGR2A H131R in 200 patients who had undergone kidney transplantation and experienced loss of graft function. FCGR2A polymorphism was related to graft survival and anti-HLA antibodies. Graft survival was calculated as the time interval between transplantation and return to chronic dialysis after transplantation. The gene frequency of FCGR2A R/R131 was found significantly more often in patients with earlier (?60months) compared to patients with later (>60months) graft failure. Overall patients homozygous for R/R131 had a significantly shorter graft survival, compared to H/H131 or H/R131 which is even more pronounced, when anti-HLA antibodies were present. These data suggest, that FCGR2A polymorphisms constitute a risk factor for graft loss following kidney transplantation and that this effect is related to anti-HLA antibodie
EVALuna2:3812

Autosomal dominant tubulointerstitial kidney disease: diagnosis, classification, and management-A KDIGO consensus report - Eckardt, Kai-Uwe; Alper, Seth L.; Antignac, Corinne; Bleyer, Anthony J.; Chauveau, Dominique; Dahan, Karin; Deltas, Constantinos; Hosking, Andrew; Kmoch, Stanislav; Rampoldi, Luca; Wiesener, Michael; Wolf, Matthias T.; et al. (Kidney International, 2015)
Rare autosomal dominant tubulointerstitial kidney disease is caused by mutations in the genes encoding uromodulin (UMOD), hepatocyte nuclear factor-1? (HNF1B), renin (REN), and mucin-1 (MUC1). Multiple names have been proposed for these disorders, including 'Medullary Cystic Kidney Disease (MCKD) type 2', 'Familial Juvenile Hyperuricemic Nephropathy (FJHN)', or 'Uromodulin-Associated Kidney Disease (UAKD)' for UMOD-related diseases and 'MCKD type 1' for the disease caused by MUC1 mutations. The multiplicity of these terms, and the fact that cysts are not pathognomonic, creates confusion. Kidney Disease: Improving Global Outcomes (KDIGO) proposes adoption of a new terminology for this group of diseases using the term 'Autosomal Dominant Tubulointerstitial Kidney Disease' (ADTKD) appended by a gene-based subclassification, and suggests diagnostic criteria. Implementation of these recommendations is anticipated to facilitate recognition and characterization of these monogenic diseases. A better understanding of these rare disorders may be relevant for the tubulointerstitial fibrosis component in many forms of chronic kidney disease.
EVALuna2:3774

Biallelic ANKS6 mutations cause late-onset ciliopathy with chronic kidney disease through YAP dysregulation - Schwarz, Hannah; Popp, Bernt; Airik, Rannar; Torabi Sarijalo, Nasrin; Knaup, Karl; Stoeckert, Johanna; Wiech, Thorsten; Amann, Kerstin Ute; Wiesmann da Silva Reis, André; Schiffer, Mario; Schueler, Markus; Wiesener, Michael (Human Molecular Genetics, 2022)
Nephronophthisis-related ciliopathies (NPHP-RC) comprises a group of inherited kidney diseases, caused by mutations in genes encoding proteins localizing to primary cilia. NPHP-RC represents one of the most frequent monogenic causes of renal failure within the first three decades of life, but its molecular disease mechanisms remain unclear. Here, we identified biallelic ANKS6 mutations in two affected siblings with late-onset chronic kidney disease by whole-exome sequencing. We employed patient-derived fibroblasts generating an in vitro model to study the precise biological impact of distinct human ANKS6 mutations, completed by immunohistochemistry studies on renal biopsy samples. Functional studies using patient-derived cells showed an impaired integrity of the ciliary inversin compartment with reduced cilia length. Further analyses demonstrated that ANKS6 deficiency leads to a dysregulation of Hippo-signaling through nuclear yes-associated protein (YAP) imbalance and disrupted ciliary localization of YAP. In addition, an altered transcriptional activity of canonical Wnt target genes and altered expression of non-phosphorylated (active) beta-catenin and phosphorylated glycogen synthase kinase 3 beta were observed. Upon ciliation, ANKS6 deficiency revealed a deranged subcellular localization and expression of components of the endocytic recycling compartment. Our results demonstrate that ANKS6 plays a key role in regulating the Hippo pathway, and ANKS6 deficiency is linked to dysregulation of signaling pathways. Our study provides molecular clues in understanding pathophysiological mechanisms of NPHP-RC and may offer new therapeutic targets.
CRIS-Team WoS Importer:2022-05-13

Biallelic Expression of Mucin-1 in Autosomal Dominant Tubulointerstitial Kidney Disease: Implications for Nongenetic Disease Recognition - Knaup, Karl; Hackenbeck, Thomas; Popp, Bernt; Stoeckert, Johanna; Wenzel, Andrea; Büttner-Herold, Maike; Pfister, Frederick; Schüler, Markus; Seven, Didem; May, Annette M.; Halbritter, Jan; Gröne, Hermann Josef; et al. (Journal of the American Society of Nephrology, 2018)
BACKGROUND: Providing the correct diagnosis for patients with tubulointerstitial kidney disease and secondary degenerative disorders, such as hypertension, remains a challenge. The autosomal dominant tubulointerstitial kidney disease (ADTKD) subtype caused by MUC1 mutations (ADTKD-MUC1) is particularly difficult to diagnose, because the mutational hotspot is a complex repeat domain, inaccessible with routine sequencing techniques. Here, we further evaluated SNaPshot minisequencing as a technique for diagnosing ADTKD-MUC1 and assessed immunodetection of the disease-associated mucin 1 frameshift protein (MUC1-fs) as a nongenetic technique. METHODS: We re-evaluated detection of MUC1 mutations by targeted repeat enrichment and SNaPshot minisequencing by haplotype reconstruction via microsatellite analysis in three independent ADTKD-MUC1 families. Additionally, we generated rabbit polyclonal antibodies against MUC1-fs and evaluated immunodetection of wild-type and mutated allele products in human kidney biopsy specimens. RESULTS: The detection of MUC1 mutations by SNaPshot minisequencing was robust. Immunostaining with our MUC1-fs antibodies and an MUC1 antibody showed that both proteins are readily detectable in human ADTKD-MUC1 kidneys, with mucin 1 localized to the apical membrane and MUC1-fs abundantly distributed throughout the cytoplasm. Notably, immunohistochemical analysis of MUC1-fs expression in clinical kidney samples facilitated reliable prediction of the disease status of individual patients. CONCLUSIONS: Diagnosing ADTKD-MUC1 by molecular genetics is possible, but it is technically demanding and labor intensive. However, immunohistochemistry on kidney biopsy specimens is feasible for nongenetic diagnosis of ADTKD-MUC1 and therefore, a valid method to select families for further diagnostics. Our data are compatible with the hypothesis that specific molecular effects of MUC1-fs underlie the pathogenesis of this disease.
EVALuna2:34428

BKPYV-SPECIFIC T CELLS REDUCE VIRAL LOAD IN A PRIMARY TUBULAR CELL MODEL - Wasielewski, E.; Lippler, Susanne; Knaup, Karl; Gary, Regina; Aigner, Michael; Kremer, Anna-Lena; Pfister, Felix; Amann, Kerstin Ute; Schiffer, Mario; Mackensen, Andreas; Wiesener, Michael (TRANSPLANT INTERNATIONAL, 2021)
CRIS-Team WoS Importer:2021-10-15

cfNOMe - A single assay for comprehensive epigenetic analyses of cell-free DNA - Erger, Florian; Nörling, Deborah; Borchert, Domenica; Leenen, Esther; Habbig, Sandra; Wiesener, Michael; Bartram, Malte P.; Wenzel, Andrea; Becker, Christian; Toliat, Mohammad R.; Nürnberg, Peter; Beck, Bodo B.; et al. (Genome Medicine, 2020)
Cell-free DNA (cfDNA) analysis has become essential in cancer diagnostics and prenatal testing. We present cfNOMe, a two-in-one method of measuring cfDNA cytosine methylation and nucleosome occupancy in a single assay using non-disruptive enzymatic cytosine conversion and a custom bioinformatic pipeline. We show that enzymatic cytosine conversion better preserves cfDNA fragmentation information than does bisulfite conversion. Whereas previously separate experiments were required to study either epigenetic marking, cfNOMe delivers reliable results for both, enabling more comprehensive and inexpensive epigenetic cfDNA profiling. cfNOMe has the potential to advance biomarker discovery and diagnostic usage in diseases with systemic perturbations of cfDNA composition.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Analysis software; Cell-free DNA; cfNOMe; Methylome; Nucleosome footprints

Complement Factor H-Related 5-Hybrid Proteins Anchor Properdin and Activate Complement at Self-Surfaces - Chen, Qian; Manzke, Melanie; Hartmann, Andrea; Büttner, Maike; Amann, Kerstin Ute; Pauly, Diana; Wiesener, Michael; Skerka, Christine; Zipfel, Peter F. (Journal of the American Society of Nephrology, 2016)
C3 glomerulopathy (C3G) is a severe kidney disease for which no specific therapy exists. The causes of C3G are heterogeneous, and defective complement regulation is often linked to C3G pathogenesis. Copy number variations in the complement factor H-related (CFHR) gene cluster on chromosome 1q32 and CFHR5 mutant proteins associate with this disease. Here, we identified CFHR5 as a pattern recognition protein that binds to damaged human endothelial cell surfaces and to properdin, the human complement activator. We found the two N-terminal short consensus repeat domains of CFHR5 contact properdin and mediate dimer formation. These properdin-binding segments are duplicated in two mutant CFHR5 proteins, CFHR2-CFHR5Hyb from German patients with C3G and CFHR5Dup from Cypriot patients with C3G. Each of these mutated proteins assembled into large multimeric complexes and, compared to CFHR5, bound damaged human cell surfaces and properdin with greater intensity and exacerbated local complement activation. This enhanced surface binding and properdin recruitment was further evidenced in the mesangia of a transplanted and explanted kidney from a German patient with a CFHR2-CFHR5Hyb protein. Enhanced properdin staining correlated with local complement activation with C3b and C5b-9 deposition on the mesangial cell surface in vitro This gain of function in complement activation for two disease-associated CFHR5 mutants describes a new disease mechanism of C3G, which is relevant for defining appropriate treatment options for this disorder.
EVALuna2:3837

Complement factor H-related hybrid protein deregulates complement in dense deposit disease - Chen, Qian; Wiesener, Michael; Eberhardt, Hannes U.; Hartmann, Andrea; Uzonyi, Barbara; Kirschfink, Michael; Amann, Kerstin Ute; Büttner, Maike; Goodship, Tim; Hugo, Christian; Skerka, Christine; Zipfel, Peter F. (Journal of Clinical Investigation, 2014)
The renal disorder C3 glomerulopathy with dense deposit disease (C3G-DDD) pattern results from complement dysfunction and primarily affects children and young adults. There is no effective treatment, and patients often progress to end-stage renal failure. A small fraction of C3G-DDD cases linked to factor H or C3 gene mutations as well as autoantibodies have been reported. Here, we examined an index family with 2 patients with C3G-DDD and identified a chromosomal deletion in the complement factor H-related (CFHR) gene cluster. This deletion resulted in expression of a hybrid CFHR2-CFHR5 plasma protein. The recombinant hybrid protein stabilized the C3 convertase and reduced factor H-mediated convertase decay. One patient was refractory to plasma replacement and exchange therapy, as evidenced by the hybrid protein quickly returning to pretreatment plasma levels. Subsequently, complement inhibitors were tested on serum from the patient for their ability to block activity of CFHR2-CFHR5. Soluble CR1 restored defective C3 convertase regulation; however, neither eculizumab nor tagged compstatin had any effect. Our findings provide insight into the importance of CFHR proteins for C3 convertase regulation and identify a genetic variation in the CFHR gene cluster that promotes C3G-DDD. Monitoring copy number and sequence variations in the CFHR gene cluster in C3G-DDD and kidney patients with C3G-DDD variations will help guide treatment strategies.
EVALuna2:3659

Correlation of Anti-HLA IgA Alloantibodies and Fc Receptor Motives with Kidney Allograft Survival - Arnold, Martin; Steffen, Ulrike; Wiesener, Michael; Bach, Christian; Spriewald, Bernd; Lindemann, Monika (Immuno, 2022)
Immunoglobulin A (IgA) is the most abundant antibody isotype in humans and anti-HLA IgA was found in sera of transplant recipients. Focusing on patients awaiting kidney re-transplantation, we tested the impact of anti-HLA-class I/II IgA antibodies on graft survival. We analyzed 276 patients with and 238 without allograft failure. Eight motives of the Fcα receptor (FCAR) and Fcγ receptor were analyzed in patients with allograft failure. The distribution of anti-HLA IgA1/A2 and IgG antibodies differed significantly (p < 0.0001) between both patient groups, and IgA1 plus IgA2 antibodies were more abundant in patients with allograft failure. Allograft survival was significantly impaired if anti-HLA-class I plus II IgA was present, in the first 105 months (9 years) of follow-up (median of 43 vs. >105 months, p = 0.007). Patients with anti-HLA IgA and IgG vs. anti-HLA IgG only had a significantly shorter allograft survival within that follow-up period (88 vs. >105 months, p = 0.008). Moreover, allograft survival was shorter (p = 0.02) in carriers of GG vs. AA + AG genotypes of FCAR rs16986050. Thus, the presence of anti-HLA IgA plus IgG vs. IgG only was associated with shorter kidney allograft survival and FCAR motives may impact on graft survival.
CRIS-Team Scopus Importer:2024-12-16
Keywords: antibodies; Fcα receptor polymorphism; Fcγ receptor polymorphism; graft survival; immunoglobulin isotypes; transplantation

Depression, Anxiety, Resilience and Coping Pre and Post Kidney Transplantation - Initial Findings from the Psychiatric Impairments in Kidney Transplantation (PI-KT)-Study - Mueller, Helge H.; Englbrecht, Matthias; Wiesener, Michael; Titze, Stephanie; Heller, Katharina; Groemer, Teja W.; Schett, Georg; Eckardt, Kai-Uwe; Kornhuber, Johannes; Maler, Juan Manuel (PLoS ONE, 2015)
Depression/anxiety, impaired Health-Related Quality of Life (HRQoL) and coping and resilience structures, are associated with increased mortality/poor outcome in chronic kidney disease (CKD) patients before (CKD/pre-KT) and after kidney (CKD-T) transplantation. Less is known about prevalence rates of psychiatric symptoms and impaired HRQoL of non-transplanted compared with transplanted patients.In a cross-sectional study comparing 101 CKD/pre-KT patients with 151 cadaveric-transplanted (CKD-T) patients, we examined prevalence of depression/anxiety (HADS questionnaire) and coping, resilience and HRQoL (SF-12, Resilience-Scale and FKV-questionnaire).The prevalence of both depressive and anxiety symptoms was not significantly different between different pre-/and CKD-T patient groups. In CKD-T no significant relations of coping strategies with kidney function were identified. Furthermore, the Resilience Scales for acceptance and competence did not suggest any differences between the CKD/pre-KT and CKD-T subgroup. In the CKD/pre-KT patients, significant correlations were identified between the acceptance subscale and partnership, as well as between the competence subscale and older age/partnership.Both the CKD/pre-KT and CKD-T patients exhibited notable impairments in the HRQoL which which showed a comparable pattern of results. KT itself does not appear to be the main risk factor for the development of mental impairments.
EVALuna2:3811

Detecting tandem repeat variants in coding regions using code-adVNTR - Park, Jonghun; Bakhtiari, Mehrdad; Popp, Bernt; Wiesener, Michael; Bafna, Vineet (iScience, 2022)
The human genome contains more than one million tandem repeats (TRs), DNA sequences containing multiple approximate copies of a motif repeated contiguously. TRs account for significant genetic variation, with 50 + diseases attributed to changes in motif number. A few diseases have been to be caused by small indels in variable number tandem repeats (VNTRs) including poly-cystic kidney disease type 1 (MCKD1) and monogenic type 1 diabetes. However, small indels in VNTRs are largely unexplored mainly due to the long and complex structure of VNTRs with multiple motifs. We developed a method, code-adVNTR, that utilizes multi-motif hidden Markov models to detect both, motif count variation and small indels, within VNTRs. In simulated data, code-adVNTR outperformed GATK-HaplotypeCaller in calling small indels within large VNTRs. We used code-adVNTR to characterize coding VNTRs in the 1000 genomes data identifying many population-specific variants, and to reliably call MUC1 mutations for MCKD1.
CRIS-Team Scopus Importer:2022-11-18
Keywords: Genetics; Genomics; Human genetics; Molecular genetics

Discordant Clinical Course of Vitamin-D-Hydroxylase (CYP24A1) Associated Hypercalcemia in Two Adult Brothers With Nephrocalcinosis - Jobst-Schwan, Tilman; Pannes, Andrea; Schlingmann, Karl Peter; Eckardt, Kai-Uwe; Beck, Bodo B.; Wiesener, Michael (Kidney & Blood Pressure Research, 2015)
Hypercalcemia can result in nephrocalcinosis/nephrolithiasis and may lead to renal failure. Idiopathic infantile hypercalcemia is caused by mutations of the CYP24A1 gene, which regulates vitamin D activity. Classically infants present with hypercalcemia. Recently, a number of individuals have been reported with late onset clinical manifestation or late diagnosis in adulthood. All these patients are believed to show hypercalciuria.We report a 24 year old patient of healthy consanguine parents. Genetic analysis was performed by Sanger sequencing of the CYP24A1 gene in the index patient and targeted exon 2 analysis of all other family members.The patient was hospitalized with severe malaise during an acute EBV-infection. He showed hypercalcemia > 3mmol/l and acute, hypovolemic renal failure with profound nephrocalcinosis, but no hypercalciuria. Genetic workup revealed a homozygous loss-of-function mutation p.E143del in the CYP24A1 gene. His clinically asymptomatic brother showed nephrocalcinosis of lesser degree. Repeatedly, low parathyroid hormone levels were detected in both brothers.This family displays the highly variable phenotype of CYP24A1 biallelic mutation carriers. CYP24A1 associated disease is an important differential diagnosis for the workup and counseling of infants as well as adults with hypercalcemia since a proper genetic diagnosis may result in therapeutic consequence
EVALuna2:3793

Dissecting TSC2-mutated renal and hepatic angiomyolipomas in an individual with ARID1B-associated intellectual disability - Popp, Bernt; Agaimy, Abbas; Kraus, Cornelia; Knaup, Karl; Ekici, Arif Bülent; Uebe, Steffen; Reis, André; Wiesener, Michael; Zweier, Christiane (BMC Cancer, 2019)
Background: Several subunits of the SWI/SNF chromatin remodeling complex are implicated in both cancer and neurodevelopmental disorders (NDD). Though there is no clinical evidence for an increased tumor risk in individuals with NDDs due to germline mutations in most of these genes so far, this has been repeatedly proposed and discussed. A young woman with NDD due to a de novo mutation in ARID1B now presented with a large renal (> 19 cm in diameter) and multiple hepatic angiomyolipomas (AMLs) but no other signs of tuberous sclerosis complex. Methods: We analyzed tumor and healthy tissue samples with exome and panel sequencing. Results: Additionally to the previously known, germline ARID1B variant we identified a post-zygotic truncating TSC2 variant in both renal and hepatic AMLs but not in any of the healthy tissues. We did not detect any further, obvious tumor driver events. The identification of a passenger variant in SIPA1L3 in both AMLs points to a common clonal origin. Metastasis of the renal AML into the liver is unlikely on the basis of discordant histopathological features. Our findings therefore point to very low-grade mosaicism for the TSC2 variant, possibly in a yet unknown mesenchymal precursor cell that expanded clonally during tumor development. A possible contribution of the germline ARID1B variant to the tumorigenesis remains unclear but cannot be excluded given the absence of any other evident tumor drivers in the AMLs. Conclusion: This unique case highlights the blurred line between tumor genetics and post-zygotic events that can complicate exact molecular diagnoses in patients with rare manifestations. It also demonstrates the relevance of multiple disorders in a single individual, the challenges of detecting low-grade mosaicisms, and the importance of proper diagnosis for treatment and surveillance.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Angiomyolipoma; ARID1B; Mosaic; Neurodevelopmental disorders; TSC2; Tuberous sclerosis complex

Diverse molecular causes of unsolved autosomal dominant tubulointerstitial kidney diseases - Wopperer, Florian; Knaup, Karl; Stanzick, Kira J.; Schneider, Karen; Jobst-Schwan, Tilman; Ekici, Arif Bülent; Uebe, Steffen; Wenzel, Andrea; Schliep, Stefan; Schürfeld, Carsten; Seitz, Randolf; Bernhardt, Wanja; et al. (Kidney International, 2022)
Autosomal Dominant Tubulointerstitial Kidney Disease (ADTKD) is caused by mutations in one of at least five genes and leads to kidney failure usually in mid adulthood. Throughout the literature, variable numbers of families have been reported, where no mutation can be found and therefore termed ADTKD-not otherwise specified. Here, we aim to clarify the genetic cause of their diseases in our ADTKD registry. Sequencing for all known ADTKD genes was performed, followed by SNaPshot minisequencing for the dupC (an additional cytosine within a stretch of seven cytosines) mutation of MUC1. A virtual panel containing 560 genes reported in the context of kidney disease (nephrome) and exome sequencing were then analyzed sequentially. Variants were validated and tested for segregation. In 29 of the 45 registry families, mutations in known ADTKD genes were found, mostly in MUC1. Sixteen families could then be termed ADTKD-not otherwise specified, of which nine showed diagnostic variants in the nephrome (four in COL4A5, two in INF2 and one each in COL4A4, PAX2, SALL1 and PKD2). In the other seven families, exome sequencing analysis yielded potential disease associated variants in novel candidate genes for ADTKD; evaluated by database analyses and genome-wide association studies. For the great majority of our ADTKD registry we were able to reach a molecular genetic diagnosis. However, a small number of families are indeed affected by diseases classically described as a glomerular entity. Thus, incomplete clinical phenotyping and atypical clinical presentation may have led to the classification of ADTKD. The identified novel candidate genes by exome sequencing will require further functional validation.
CRIS-Team Scopus Importer:2022-07-15
Keywords: ADTKD; Alport syndrome; exome; MITKD; MUC1; UMOD

Donor treatment with a PHD-inhibitor activating HIFs prevents graft injury and prolongs survival in an allogenic kidney transplant model - Bernhardt, W. M.; Gottmann, U.; Doyon, F.; Buchholz, Björn; Campean, Valentina; Schödel, Johannes; Reisenbuechler, A.; Klaus, S.; Arend, M.; Flippin, L.; Willam, Carsten; Yard, B.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2009)
Long-term survival of renal allografts depends on the chronic immune response and is probably influenced by the initial injury caused by ischemia and reperfusion. Hypoxia-inducible transcription factors (HIFs) are essential for adaptation to low oxygen. Normoxic inactivation of HIFs is regulated by oxygen-dependent hydroxylation of specific prolyl-residues by prolyl-hydroxylases (PHDs). Pharmacological inhibition of PHDs results in HIF accumulation with subsequent activation of tissue-protective genes. We examined the effect of donor treatment with a specific PHD inhibitor (FG-4497) on graft function in the Fisher-Lewis rat model of allogenic kidney transplantation (KTx). Orthotopic transplantation of the left donor kidney was performed after 24 h of cold storage. The right kidney was removed at the time of KTx (acute model) or at day 10 (chronic model). Donor animals received a single dose of FG-4497 (40 mg/kg i.v.) or vehicle 6 h before donor nephrectomy. Recipients were followed up for 10 days (acute model) or 24 weeks (chronic model). Donor preconditioning with FG-4497 resulted in HIF accumulation and induction of HIF target genes, which persisted beyond cold storage. It reduced acute renal injury (serum creatinine at day 10: 0.66 +/- 0.20 vs. 1.49 +/- 1.36 mg/dL; P < 0.05) and early mortality in the acute model and improved long-term survival of recipient animals in the chronic model (mortality at 24 weeks: 3 of 16 vs. 7 of 13 vehicle-treated animals; P < 0.05). In conclusion, pretreatment of organ donors with FG-4497 improves short-and long-term outcomes after allogenic KTx. Inhibition of PHDs appears to be an attractive strategy for organ preservation that deserves clinical evaluation.
Keywords: hypoxia-inducible transcription factors; kidney injury; protection; transplantation

Estrogen-mediated downregulation of HIF-1 alpha signaling in B lymphocytes influences postmenopausal bone loss - Meng, Xianyi; Lin, Zhen; Cao, Shan; Janowska, Iga; Sonomoto, Koshiro; Andreev, Darja; Knab, Katharina; Wen, Jinming; Knaup, Karl; Krönke, Gerhard; Rizzi, Marta; Schett, Georg; et al. (Bone Research, 2022)
In the bone marrow, B cells and bone-resorbing osteoclasts colocalize and form a specific microenvironment. How B cells functionally influence osteoclasts and bone architecture is poorly understood. Using genetically modified mice and high-throughput analyses, we demonstrate that prolonged HIF-1 alpha signaling in B cells leads to enhanced RANKL production and osteoclast formation. In addition, deletion of HIF-1 alpha in B cells prevents estrogen deficiency-induced bone loss in mice. Mechanistically, estrogen controls HIF-1 alpha protein stabilization through HSP70-mediated degradation in bone marrow B cells. The stabilization of HIF-1 alpha protein in HSP70-deficient bone marrow B cells promotes RANKL production and osteoclastogenesis. Induction of HSP70 expression by geranylgeranylacetone (GGA) administration alleviates ovariectomy-induced osteoporosis. Moreover, RANKL gene expression has a positive correlation with HIF1A expression in human B cells. In conclusion, HIF-1 alpha signaling in B cells is crucial for the control of osteoclastogenesis, and the HSP70/HIF-1 alpha axis may serve as a new therapeutic target for osteoporosis.
CRIS-Team WoS Importer:2022-03-04

Excellent efficacy and beneficial safety during observational 5-year follow-up of rapid steroid withdrawal after renal transplantation (Harmony FU study) - Stumpf, Julian; Thomusch, Oliver; Opgenoorth, Mirian; Wiesener, Michael; Pascher, Andreas; Woitas, Rainer Peter; Suwelack, Barbara; Rentsch, Markus; Witzke, Oliver; Rath, Thomas; Banas, Bernhard; Benck, Urs; et al. (Nephrology Dialysis Transplantation, 2024)
Background: We previously reported excellent efficacy and improved safety aspects of rapid steroid withdrawal (RSWD) in the randomized controlled 1-year "Harmony"trial with 587 predominantly deceased-donor kidney transplant recipients randomized either to basiliximab or rabbit antithymocyte globulin induction therapy and compared with standard immunosuppressive therapy consisting of basiliximab, low tacrolimus once daily, mycophenolate mofetil and corticosteroids. Methods: The 5-year post-trial follow-up (FU) data were obtained in an observational manner at a 3- and a 5-year visit only for those Harmony patients who consented to participate and covered clinical events that occurred from the second year onwards. Results: Biopsy-proven acute rejection and death-censored graft loss rates remained low and independent of RSWD. Rapid steroid withdrawal was an independent positive factor for patient survival (adjusted hazard ratio 0.554, 95% confidence interval 0.314-0.976; P =. 041). The reduced incidence of post-transplantation diabetes mellitus in RSWD patients during the original 1-year study period was not compensated by later incidences during FU. Incidences of other important outcome parameters such as opportunistic infections, malignancies, cardiovascular morbidity/risk factors, donor-specific antibody formation or kidney function did not differ during FU period. Conclusions: With all the limitations of a post-trial FU study, the Harmony FU data confirm excellent efficacy and beneficial safety aspects of RSWD under modern immunosuppressive therapy over the course of 5 years after kidney transplantation in an immunologically low-risk, elderly population of Caucasian kidney transplant recipients.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Harmony study; long-term follow-up; mortality; rapid steroid withdrawal; renal transplantation

Experience with belatacept rescue therapy in kidney transplant recipients - Brakemeier, Susanne; Kannenkeril, Dennis; Duerr, Michael; Braun, Timm; Bachmann, Friederike; Schmidt, Danilo; Wiesener, Michael; Budde, Klemens (Transplant International, 2016)
In kidney transplant recipients with chronic graft dysfunction, long-term immunosuppression with calcineurin inhibitors (CNIs) or mTOR inhibitors (mTORi) can be challenging due to adverse effects, such as nephrotoxicity and proteinuria. Seventy-nine kidney transplant recipients treated with CNI-based or mTORi-based maintenance immunosuppression who had CNI-induced nephrotoxicity or severe adverse events were switched to belatacept. Mean time from transplantation to belatacept conversion was 69.0 months. Mean estimated glomerular filtration rate (eGFR) ± standard deviation at baseline was 26.1 ± 15.0 ml/min/1.73 m(2) , increasing to 34.0 ± 15.2 ml/min/1.73 m(2) at 12 months postconversion (P < 0.0005). Renal function improvements were also seen in patients with low eGFR (<25 ml/min/1.73 m(2) ) or high proteinuria (>500 mg/l) at conversion. The Kaplan-Meier estimates for patient and graft survival at 12 months were 95.0% and 85.6%, respectively. The discontinuation rate due to adverse events was 7.9%. One case of post-transplant lymphoproliferative disorder occurred at 17 months postconversion. For comparison, a historical control group of 41 patients converted to mTORi-based immunosuppression because of biopsy-confirmed CNI-induced toxicity was examined; eGFR increased from 27.6 ± 7.2 ml/min/1.73 m(2) at baseline to 31.1 ± 11.9 ml/min/1.73 m(2) at 12 months (P = 0.018). Belatacept-based immunosuppression may be an alternative regimen for kidney transplant recipients with CNI- or mTORi-induced toxicity.
EVALuna2:3933

FHR5 Binds to Laminins, Uses Separate C3b and Surface-Binding Sites, and Activates Complement on Malondialdehyde-Acetaldehyde Surfaces - Rudnick, Ramona B.; Chen, Qian; Stea, Emma Diletta; Hartmann, Andrea; Papac-Milicevic, Nikolina; Person, Fermin; Wiesener, Michael; Binder, Christoph J.; Wiech, Thorsten; Skerka, Christine; Zipfel, Peter F. (Journal of Immunology, 2018)
Factor H related-protein 5 (CFHR5) is a surface-acting complement activator and variations in the CFHR5 gene are linked to CFHR glomerulonephritis. In this study, we show that FHR5 binds to laminin-521, the major constituent of the glomerular basement membrane, and to mesangial laminin-211. Furthermore, we identify malondialdehyde-acetaldehyde (MAA) epitopes, which are exposed on the surface of human necrotic cells (Homo sapiens), as new FHR5 ligands. Using a set of novel deletion fragments, we show that FHR5 binds to laminin-521, MAA epitopes, heparin, and human necrotic cells (HUVECs) via the middle region [short consensus repeats (SCRs) 5-7]. In contrast, surface-bound FHR5 contacts C3b via the C-terminal region (SCRs8-9). Thus, FHR5 uses separate domains for C3b binding and cell surface interaction. MAA epitopes serve as a complement-activating surface by recruiting FHR5. The complement activator FHR5 and the complement inhibitor factor H both bind to oxidation-specific MAA epitopes and FHR5 competes with factor H for binding. The C3 glomerulopathy-associated FHR21-2-FHR5 hybrid protein is more potent in MAA epitope binding and activation compared with wild-type FHR5. The implications of these results for pathology of CFHR glomerulonephritis are discussed. In conclusion, we identify laminins and oxidation-specific MAA epitopes as novel FHR5 ligands and show that the surface-binding site of FHR5 (SCRs5-7) is separated from the C3b binding site (SCRs8-9). Furthermore, FHR5 competes with factor H for binding to MAA epitopes and activates complement on these modified structures.
EVALuna2:34259

HIF-1 or HIF-2 induction is sufficient to achieve cell cycle arrest in NIH3T3 mouse fibroblasts independent from hypoxia - Hackenbeck, Thomas; Knaup, Karl; Schietke, Ruth; Schödel, Johannes; Willam, Carsten; Wu, Xiaoqing; Warnecke, Christina; Eckardt, Kai-Uwe; Wiesener, Michael Sean (Cell Cycle, 2009)
Hypoxia is a severe stress which induces physiological and molecular adaptations, where the latter is dominated by the Hypoxia-inducible transcription Factor (HIF). A well described response on cellular level upon exposure to hypoxia is a reversible cell cycle arrest, which probably renders the cells more resistant to the difficult environment. The individual roles of hypoxia itself and of the isoforms HIF-1α and HIF-2α in cell cycle regulation are poorly understood and discussed controversially. In order to characterize the isolated effect of both HIFα isoforms on the cell cycle we generated tetracycline inducible, HIF-1α and -2α expressing NIH3T3 cells. The cDNAs for HIFα were mutated to generate stable and active HIF under normoxia. Upon activation of both HIFα subunits, the total number of living cells was reduced and long-term stimulation of HIF led to complete loss of transgene expression, implicating a strong negative selection pressure. Equally, colony forming activity was reduced by activation of both HIFα subunits. Cell cycle analyses showed that HIF activation resulted in a prominent cell cycle arrest in G1-phase, similarly to the hypoxic effect. Both, HIF-1α and HIF-2α were able to induce the expression of the cyclin-dependent kinase inhibitor p27 on reporter gene and protein level. Our study shows that HIF-1 and HIF-2 can individually arrest the cell cycle independent from hypoxia. These findings have implications for the resistance of tumor cells to the environment and treatment, but also for physiological cells. Importantly, recent approaches to stabilize HIFα in normoxia could have deleterious effects on proliferating tissues. ©2009 Landes Bioscience.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Cell cycle regulation; G; Hypoxia; Hypoxia-inducible factor (HIF); p27; Tetracycline-inducible; Tumor resistance; Tumorigenesis; VHL

HIF activation protects from acute kidney injury - Weidemann, Alexander; Bernhardt, Wanja M.; Klanke, Bernd; Daniel, Christoph; Buchholz, Björn; Campean, Valentina; Amann, Kerstin Ute; Warnecke, Christina; Wiesener, Michael Sean; Eckardt, Kai-Uwe; Willam, Carsten (Journal of the American Society of Nephrology, 2008)
The contribution of hypoxia to cisplatin-induced renal tubular injury is controversial. Because the hypoxia-inducible factor (HIF) pathway is a master regulator of adaptation to hypoxia, we measured the effects of cisplatin on HIF accumulation in vitro and in vivo, and tested whether hypoxic preconditioning is protective against cisplatin-induced injury. We found that cisplatin did not stabilize HIF-1 alpha protein in vitro or in vivo under normoxic conditions. However, hypoxic preconditioning of cisplatin-treated proximal tubular cells in culture reduced apoptosis in an HIF-1 alpha-dependent fashion and increased cell proliferation as measured by BrdU incorporation. In vivo, rats preconditioned with carbon monoxide before cisplatin administration had significantly better renal function than rats kept in normoxic conditions throughout. Moreover, the histomorphological extent of renal damage and tubular apoptosis was reduced by the preconditional treatment. Therefore, development of pharmacologic agents to induce renal HIF might provide a new approach to ameliorate cisplatin-induced nephrotoxicity.

HIF is not essential for suppression of experimental tumor growth by mTOR inhibition - Knaup, Karl; Günther, Regina; Stoeckert, Johanna; Monti, Juliana M.; Eckardt, Kai-Uwe; Wiesener, Michael (Journal of Cancer, 2017)
The Hypoxia Inducible Transcription Factor (HIF) is the master regulator of cellular response to hypoxic adaptation. Solid tumors inevitably harbour hypoxic regions with subsequent stabilization and activation of HIF and HIF target genes due to poor vascularization and rapid growth. The mammalian target of rapamycin (mTOR) is a global regulator of cellular growth and proliferation, which can also regulate HIF expression independantly of hypoxia via specific activation of cellular translation and transcription. An effective blockade of mTOR results in attenuation of HIF under hypoxic conditions in vitro. This mechanism could enable a simultaneous inhibition of both the mTOR- and the HIF-pathway, resulting in an effective tool for cancer targeting. We set out to analyze the effect of mTOR inhibition and the involvement of mTOR regulation on HIF in vivo in a subcutaneous xenograft model in nude mice. Our results demonstrate that mTOR inhibition in our model leads to a clear reduction in tumor growth of various cellular origins, most likely due to inhibition of cellular proliferation. Moreover, these effects can also be achieved independently of the HIF status of the tumor cells. The HIF levels per se seem to remain unaffected by mTOR inhibition, probably due to the profound hypoxic environment in these threedimensional structures, consequently leading to a strong HIF stabillization. Therefore, treatment of these experimental tumors with mTOR inhibitors is an effective tool to achieve size regression. The involvement of and the effect on HIF in this in vivo setting is nevertheless negligible.
EVALuna2:3992

How long should aHUS be treated? Wie lange sollte aHUS behandelt werden? - Wiesener, Michael (Nephrologe, 2021)
CRIS-Team Scopus Importer:2021-08-20

Hypoxia controls expression of kidney-pathogenic MUC1 variants - Naas, Stephanie; Krüger, René; Knaup, Karl; Naas, Julia; Grampp, Steffen; Schiffer, Mario; Wiesener, Michael; Schödel, Johannes (Life Science Alliance, 2023)
The interplay between genetic and environmental factors influences the course of chronic kidney disease (CKD). In this context, genetic alterations in the kidney disease gene MUC1 (Mucin1) predispose to the development of CKD. These variations comprise the polymorphism rs4072037, which alters splicing of MUC1 mRNA, the length of a region with variable number of tandem repeats (VNTR), and rare autosomal-dominant inherited dominant-negative mutations in or 59 to the VNTR that causes autosomal dominant tubulointerstitial kidney disease (ADTKD-MUC1). As hypoxia plays a pivotal role in states of acute and chronic kidney injury, we explored the effects of hypoxia-inducible transcription factors (HIF) on the expression of MUC1 and its pathogenic variants in isolated primary human renal tubular cells. We defined a HIF-binding DNA regulatory element in the promoter-proximal region of MUC1 from which hypoxia or treatment with HIF stabilizers, which were recently approved for an anti-anemic therapy in CKD patients, increased levels of wild-type MUC1 and the disease-associated variants. Thus, application of these compounds might exert unfavorable effects in patients carrying MUC1 risk variants.
CRIS-Team Scopus Importer:2023-08-11

Hypoxia-inducible factor-1α is a critical transcription factor for IL-10-producing B cells in autoimmune disease - Meng, Xianyi; Groetsch, Bettina; Luo, Yubin; Knaup, Karl; Wiesener, Michael; Chen, Xiao-Xiang; Jantsch, Jonathan; Fillatreau, Simon; Schett, Georg; Bozec, Aline (Nature Communications, 2018)
Hypoxia-inducible factors (HIFs) are key elements for controlling immune cell metabolism and functions. While HIFs are known to be involved in T cells and macrophages activation, their functions in B lymphocytes are poorly defined. Here, we show that hypoxia-inducible factor-1? (HIF-1?) contributes to IL-10 production by B cells. HIF-1? regulates IL-10 expression, and HIF-1?-dependent glycolysis facilitates CD1dhiCD5+ B cells expansion. Mice with B cell-specific deletion of Hif1a have reduced number of IL-10-producing B cells, which result in exacerbated collagen-induced arthritis and experimental autoimmune encephalomyelitis. Wild-type CD1dhiCD5+ B cells, but not Hif1a-deficient CD1dhiCD5+ B cells, protect recipient mice from autoimmune disease, while the protective function of Hif1a-deficient CD1dhiCD5+ B cells is restored when their defective IL-10 expression is genetically corrected. Taken together, this study demonstrates the key function of the hypoxia-associated transcription factor HIF-1? in driving IL-10 expression in CD1dhiCD5+ B cells, and in controlling their protective activity in autoimmune disease.
EVALuna2:13529

Hypoxia-inducible protein 2 is a novel lipid droplet protein and a specific target gene of hypoxia-inducible factor-1 - Gimm, Tina; Wiese, Melanie; Teschemacher, Barbara; Deggerich, Anke; Schödel, Johannes; Knaup, Karl; Hackenbeck, Thomas; Hellerbrand, Claus; Amann, Kerstin Ute; Wiesener, Michael; Höning, Stefan; Eckardt, Kai-Uwe; et al. (The FASEB Journal, 2010)
Hypoxia-inducible protein 2 (HIG2) has been implicated in canonical Wnt signaling, both as target and activator. The potential link between hypoxia and an oncogenic signaling pathway might play a pivotal role in renal clear-cell carcinoma characterized by constitutive activation of hypoxia-inducible factors (HIFs), and hence prompted us to analyze HIG2 regulation and function in detail. HIG2 was up-regulated by hypoxia and HIF inducers in all cell types and mouse organs investigated and abundantly expressed in renal clear-cell carcinomas. Promoter analyses, gel shifts, and siRNA studies revealed that HIG2 is a direct and specific target of HIF-1, but not responsive to HIF-2. Surprisingly, HIG2 was not secreted, and HIG2 overexpression neither stimulated proliferation nor activated Wnt signaling. Instead, we show that HIG2 decorates the hemimembrane of lipid droplets, whose number and size increase on hypoxic inhibition of fatty acid β-oxidation, and colocalizes with the lipid droplet proteins adipophilin and TIP47. Normoxic overexpression of HIG2 was sufficient to increase neutral lipid deposition in HeLa cells and stimulated cytokine expression. HIG2 could be detected in atherosclerotic arteries and fatty liver disease, suggesting that this ubiquitously inducible HIF-1 target gene may play an important functional role in diseases associated with pathological lipid accumulation. © FASEB.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Gene expression; Lipid metabolism; Promoter; Renal clear-cell carcinoma

Hypoxia-inducible transcription factors stabilization in the thick ascending limb protects against ischemic acute kidney injury - Schley, Gunnar; Klanke, Bernd; Schödel, Johannes; Forstreuter, Frauke; Shukla, Deepa; Kurtz, Armin; Amann, Kerstin Ute; Wiesener, Michael; Rosen, Seymour; Eckardt, Kai-Uwe; Maxwell, Patrick H.; Willam, Carsten (Journal of the American Society of Nephrology, 2011)
Hypoxia-inducible transcription factors (HIF) protect cells against oxygen deprivation, and HIF stabilization before ischemia mitigates tissue injury. Because ischemic acute kidney injury (AKI) often involves the thick ascending limb (TAL), modulation of HIF in this segment may be protective. Here, we generated mice with targeted TAL deletion of the von Hippel-Lindau protein (Vhl), which mediates HIF degradation under normoxia, using Tamm-Horsfall protein (Thp)-driven Cre expression. These mice showed strong expression of HIF-1α in TALs but no changes in kidney morphology or function under control conditions. Deficiency of Vhl in the TAL markedly attenuated proximal tubular injury and preserved TAL function following ischemia-reperfusion, which may be partially a result of enhanced expression of glycolytic enzymes and lactate metabolism. These results highlight the importance of the thick ascending limb in the pathogenesis of AKI and suggest that pharmacologically targeting the HIF system may have potential to prevent and mitigate AKI. Copyright © 2011 by the American Society of Nephrology.
CRIS-Team Scopus Importer:2024-05-13

Hypoxia inhibits nephrogenesis through paracrine Vegfa despite the ability to enhance tubulogenesis - Schley, Gunnar; Scholz, Holger; Kraus, Andre; Hackenbeck, Thomas; Klanke, Bernd; Willam, Carsten; Wiesener, Michael; Heinze, Eva; Burzlaff, Nicolai; Eckardt, Kai-Uwe; Buchholz, Björn (Kidney International, 2015)
Reduced nephron number predisposes to hypertension and kidney disease. Interaction of the branching ureteric bud and surrounding mesenchymal cells determines nephron number. Since oxygen supply may be critical for intrauterine development, we tested whether hypoxia and hypoxiainducible factor-1 alpha (HIF-1 alpha) influence nephrogenesis. We found that HIF-1 alpha is required for branching of MDCK cells. In addition, culture of metanephric mouse kidneys with ureteric bud cell-specific stabilization or knockout of HIF-1 alpha revealed a positive impact of HIF-1 alpha on nephrogenesis. In contrast, widespread stabilization of HIF-1 alpha in metanephric kidneys through hypoxia or HIF stabilizers impaired nephrogenesis, and pharmacological HIF inhibition enhanced nephrogenesis. Several lines of evidence suggest an inhibitory effect through the hypoxia response of mesenchymal cells. HIF-1 alpha was expressed in mesenchymal cells during nephrogenesis. Expression of the anti-branching factors Bmp4 and Vegfa, secreted by mesenchymal cells, was increased upon HIF stabilization. The conditioned medium from hypoxic metanephric kidneys inhibited MDCK branching, which was partially rescued by Vegfa antibodies. Thus, the effect of HIF-1 alpha on nephrogenesis appears context dependent. While HIF-1 alpha in the ureteric bud is of importance for proper branching morphogenesis, the net effect of hypoxia-induced HIF activation in the embryonic kidney appears to be mesenchymal cell-dependent inhibition of ureter branching.
EVALuna2:3775
Keywords: hypoxia; hypoxia-inducible factor-1 alpha; kidney development; metanephric mesenchyme; nephrogenesis; Vegfa

Hypoxia regulates the sperm associated antigen 4 (SPAG4) via HIF, which is expressed in renal clear cell carcinoma and promotes migration and invasion in vitro - Knaup, Karl; Monti, Juliana; Hackenbeck, Thomas; Jobst-Schwan, Tilman; Klanke, Bernd; Schietke, Ruth Elisabeth; Wacker, Ingrid; Behrens, Jürgen; Amann, Kerstin Ute; Eckardt, Kai-Uwe; Warnecke, Christina; Wiesener, Michael (Molecular Carcinogenesis, 2014)
Hypoxia leads to the upregulation of a variety of genes mediated largely via the hypoxia inducible transcription factor (HIF). Prominent HIF-regulated target genes such as the vascular endothelial growth factor (VEGF), the glucose transporter 1 (Glut-1), or erythropoietin (EPO) help to assure survival of cells and organisms in a low oxygenated environment. Here, we are the first to report the hypoxic regulation of the sperm associated antigen 4 (SPAG4). SPAG4 is a member of the cancer testis (CT) gene family and to date little is known about its physiological function or its involvement in tumor biology. A number of CT family candidate genes are therefore currently being investigated as potential cancer markers, due to their predominant testicular expression pattern. We analyzed RNA and protein expression by RNAse protection assay, immunoflurescent as well as immunohistological stainings. To evaluate the influence of SPAG4 on migration and invasion capabilities, siRNA knockdown as well as transient overexpression was performed prior to scratch or invasion assay analysis. The hypoxic regulation of SPAG4 is clearly mediated in a HIF-1 and VHL dependent manner. We furthermore show upregulation of SPAG4 expression in human renal clear cell carcinoma (RCC) and co-localization within the nucleolus in physiological human testis tissue. SPAG4 knockdown reduces the invasion capability of RCC cells in vitro and overexpression leads to enhancement of tumor cell migration. Together, SPAG4 could possibly play a role in the invasion capability and growth of renal tumors and could represent an interesting target for clinical intervention. © 2013 Wiley Periodicals, In
EVALuna2:3620

Induction therapy with rabbit antithymocyte globulin versus basiliximab after kidney transplantation: a health economic analysis from a German perspective - Cremaschi, Liana; von Versen, Regina; Benzing, Thomas; Wiesener, Michael; Zink, Nikolai; Milkovich, Gary; Paivanas, Thomas; Gallagher, Meghan; Thaiss, Friedrich (Transplant International, 2017)
A health economic analysis was undertaken based on the 1-year database from a randomized study of rabbit anti-human thymocyte immunoglobulin (rATG) versus basiliximab, in kidney transplantation using resource utilization data and cost estimates from three German hospitals. A three-state Markov model was applied to estimate cost-effectiveness to 10 years post-transplant. Total mean treatment cost per patient to year 1 post-transplant was EUR62 075 vs. EUR59 767 for rATG versus basiliximab (P < 0.01). rATG therapy was associated with similar treatment costs to basiliximab by year 2, and a predicted cumulative treatment cost saving of EUR4 259 under rATG versus basiliximab by year 10 post-transplant. The mean number of quality-adjusted life years (QALYs) per patient by year 1 was 0.809 vs. 0.802 in the rATG and basiliximab cohorts, respectively (P = 0.38), with cumulative QALYs of 6.161 and 6.065 per patient by year 10. By year 2, the cumulative cost per QALY was slightly lower under rATG (EUR35 378) than basiliximab (EUR35 885), progressing to a saving of EUR1 041 under rATG for the cumulative cost per QALY by year 10. In conclusion, this model indicates that rATG induction provides a modest increase in QALYs with lower long-term costs than basiliximab in deceased-donor high-risk kidney transplant patient
EVALuna2:3963

Is Early Complement Activation in Renal Transplantation Associated with Later Graft Outcome? - Bobka, Steffen; Ebert, Nadja; Koertvely, Eloed; Jacobi, Johannes; Wiesener, Michael; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Kidney & Blood Pressure Research, 2018)
BACKGROUND/AIMS: Complement activation is important in post-transplantation renal injury, but data on its role as predictor of transplant outcome/complications when assessed in donor kidneys are lacking. METHODS: In human renal transplant biopsies with delayed graft function (DGF, n=12), antibody mediated rejection (ABMR, n=8), T-cell mediated rejection (TCMR, n=11), 1 year protocol biopsies (control, n=10) and corresponding zero-biopsies we performed immunohistochemical analyses of 6 complement factors using FFPE sections and correlated the findings with kidney function, as assessed by serum creatinine, and morphological changes including interstitial fibrosis and tubular atrophy (IF/TA). RESULTS: In DGF, TCMR and ABMR significant complement deposition was observed, which was less pronounced in corresponding zero-biopsies. Zero-biopsies with subsequent ABMR showed glomerular complement factor D and C3c expression. Moreover, glomerular C3c and C9 and tubular MASP-2 and Collectin-11 expression in zero-biopsies significantly correlated with serum creatinine at diagnosis of DGF, TCMR or ABMR. Glomerular C1q was significantly increased in ABMR, but not in DGF and TCMR. In contrast, peritubular C1q was significantly enhanced in DGF and TCMR compared to zero-biopsies. Using C3d as a surrogate marker for complement activity we could confirm that stained complement factors are frequently associated with complement activity. CONCLUSION: Complement deposition strongly correlated with histopathological changes observed in renal transplants. All 3 complement pathways were operational in biopsies with DGF, TCMR and ABMR albeit with differential abundance and localization. Since complement deposition in zero-biopsies correlated with graft function and morphological changes, early specific complement inhibition in renal transplantation may be a new therapeutic option to prevent graft loss.
EVALuna2:35394

Kidney-transplant patients receiving living- or dead-donor organs have similar psychological outcomes (findings from the PI-KT study) - Müller, Helge H.O.; Lücke, Caroline; Englbrecht, Matthias; Wiesener, Michael; Siller, Teresa; Eckardt, Kai-Uwe; Kornhuber, Johannes; Maler, Juan Manuel (Mental Illness, 2020)
Purpose: Kidney transplantation (KT) is the treatment of choice for end-stage chronic kidney disease (CKD) and is well known to improve the clinical outcome of patients. However, the impact of KT on comorbid psychological symptoms, particularly depression and anxiety, is less clear, and recipients of living-donor (LD) organs may have a different psychological outcome from recipients of dead-donor (DD) organs. Design/methodology/approach: In total, 152 patients were included and analyzed using a cross-sectional design. Of these patients, 25 were pre-KT, 13 were post-KT with a LD transplant and 114 were post-KT with a DD transplant. The patients were tested for a variety of psychometric outcomes using the Hospital Anxiety and Depression Scale, the 12-Item Short Form Health Survey (assessing physical and mental health-related quality of life), the Resilience Scale, the Coping Self-Questionnaire and the Social Support Questionnaire. Findings: The mean age of the patients was 51.25 years and 40 per cent of the patients were female. As expected, the post-KT patients had significantly better scores on the physical component of the Short Form Health Survey than the pre-KT patients, and there were no significant differences between the two post-KT groups. There were no significant differences among the groups in any of the other psychometric outcome parameters tested, including anxiety, depression and the mental component of health-related quality of life. Research limitations/implications: KT and the origin of the donor organ do not appear to have a significant impact on the psychological well-being of transplant patients with CKD. Although the diagnosis and early treatment of psychological symptoms, such as depression and anxiety, remain important for these patients, decisions regarding KT, including the mode of transplantation, should not be fundamentally influenced by concerns about psychological impairments at the population level. Originality/value: CKD is a serious condition involving profound impairment of the physical and psychological well-being of patients. KT is considered the treatment of choice for most of these patients. KT has notable advantages over dialysis with regard to the long-term physical functioning of the renal and cardiovascular system and increases the life expectancy of patients. However, the data on the improvement of psychological impairments after KT are less conclusive.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Coping; Kidney transplantation

Molecular diagnosis of kidney transplant failure based on urine - Wiesener, Antje; Knaup, Karl; Büttner-Herold, Maike; Dieterle, Anne; Stoeckert, Johanna; Riedl, Bernhard; Morath, Christian; Wald, Alexandra; Vondran, Florian; Braun, Felix; Schödel, Johannes; Schüler, Markus; et al. (American Journal of Transplantation, 2020)
In light of the organ shortage, there is a great responsibility to assess postmortal organs for which procurement has been consented and to increase the life span of transplanted organs. The former responsibility has moved many centers to accept extended criteria organs. The latter responsibility requires an exact diagnosis and, if possible, omission of the harmful influence on the transplant. We report the course of a kidney transplant that showed a steady decline of function over a decade, displaying numerous cysts of different sizes. Clinical workup excluded the most frequent causes of chronic transplant failure. The filed allocation documents mentioned the donor's disease of oral-facial-digital syndrome, a rare ciliopathy, which can also affect the kidney. Molecular diagnosis was performed by culturing donor tubular cells from the recipient ' s urine more than 10 years after transplantation. Next-generation panel sequencing with DNA from tubular urinary cells revealed a novel truncating mutation in OFD1, which sufficiently explains the features of the kidney transplants, also found in the second kidney allograft. Despite this severe donor disease, lifesaving transplantation with good long-term outcome was enabled for 5 recipients.
CRIS-Team WoS Importer:2020-01-31

Monitoring complement biomarkers in C3 glomerulopathy patients with factor H or FHR gene mutations before and after treatment with eculizumab or ravulizumab - Vanderliek, Kim; Afonso, Sara; Loeschmann, Ina; Krebs, Christian; Wiech, Thorsten; Skerka, Christine; Zipfel, Peter; Wiesener, Michael (MOLECULAR IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2022-04-29

Mutations in mitochondrial DNA causing tubulointerstitial kidney disease - Connor, Thomas M.; Hoer, Simon; Mallett, Andrew; Gale, Daniel P.; Gomez-Duran, Aurora; Posse, Viktor; Antrobus, Robin; Moreno, Pablo; Sciacovelli, Marco; Frezza, Christian; Duff, Jennifer; Sheerin, Neil S.; et al. (PLoS Genetics, 2017)
Tubulointerstitial kidney disease is an important cause of progressive renal failure whose aetiology is incompletely understood. We analysed a large pedigree with maternally inherited tubulointerstitial kidney disease and identified a homoplasmic substitution in the control region of the mitochondrial genome (m.547A>T). While mutations in mtDNA coding sequence are a well recognised cause of disease affecting multiple organs, mutations in the control region have never been shown to cause disease. Strikingly, our patients did not have classical features of mitochondrial disease. Patient fibroblasts showed reduced levels of mitochondrial tRNAPhe, tRNALeu1 and reduced mitochondrial protein translation and respiration. Mitochondrial transfer demonstrated mitochondrial transmission of the defect and in vitro assays showed reduced activity of the heavy strand promoter. We also identified further kindreds with the same phenotype carrying a homoplasmic mutation in mitochondrial tRNAPhe (m.616T>C). Thus mutations in mitochondrial DNA can cause maternally inherited renal disease, likely mediated through reduced function of mitochondrial tRNAPhe.
EVALuna2:3945

Mutations in PIK3C2A cause syndromic short stature, skeletal abnormalities, and cataracts associated with ciliary dysfunction - Tiosano, Dov; Baris, Hagit N.; Chen, Anlu; Hitzert, Marrit M.; Schüler, Markus; Gulluni, Federico; Wiesener, Antje; Bergua, Antonio; Mory, Adi; Copeland, Brett; Gleeson, Joseph G.; Rump, Patrick; et al. (PLoS Genetics, 2019)
PIK3C2A is a class II member of the phosphoinositide 3-kinase (PI3K) family that catalyzes the phosphorylation of phosphatidylinositol (PI) into PI(3)P and the phosphorylation of PI(4)P into PI(3,4)P2. At the cellular level, PIK3C2A is critical for the formation of cilia and for receptor mediated endocytosis, among other biological functions. We identified homozygous loss-of-function mutations in PIK3C2A in children from three independent consanguineous families with short stature, coarse facial features, cataracts with secondary glaucoma, multiple skeletal abnormalities, neurological manifestations, among other findings. Cellular studies of patient-derived fibroblasts found that they lacked PIK3C2A protein, had impaired cilia formation and function, and demonstrated reduced proliferative capacity. Collectively, the genetic and molecular data implicate mutations in PIK3C2A in a new Mendelian disorder of PI metabolism, thereby shedding light on the critical role of a class II PI3K in growth, vision, skeletal formation and neurological development. In particular, the considerable phenotypic overlap, yet distinct features, between this syndrome and Lowe's syndrome, which is caused by mutations in the PI-5-phosphatase OCRL, highlight the key role of PI metabolizing enzymes in specific developmental processes and demonstrate the unique non-redundant functions of each enzyme. This discovery expands what is known about disorders of PI metabolism and helps unravel the role of PIK3C2A and class II PI3Ks in health and disease.
CRIS-Team Scopus Importer:2019-05-28

Noninvasive Diagnosis of Acute Rejection in Renal Transplant Patients Using Mass Spectrometric Analysis of Urine Samples: A Multicenter Diagnostic Phase III Trial - Gwinner, Wilfried; Karch, Annika; Braesen, Jan H.; Khalifa, Abedalrazag A.; Metzger, Jochen; Naesens, Maarten; Van Loon, Elisabet; Anglicheau, Dany; Marquet, Pierre; Budde, Klemens; Matz, Mareen; Arns, Wolfgang; et al. (Transplantation Direct, 2022)
Background. Timely recognition and treatment of acute kidney graft rejection is important to prevent premature graft failure. A predefined urinary marker set for acute T cell-mediated rejection (TCMR) containing 14 peptides was tested for this purpose in a multicenter in-place validation study. Methods. Three hundred twenty-nine prospectively collected and 306 archived urine samples from 11 transplant centers in Germany, France, and Belgium were examined. Samples were taken immediately before a biopsy, performed for graft dysfunction within the first transplant year. Primary outcomes were sensitivity and specificity of the marker set for the diagnosis of biopsy-proven acute TCMR, with prespecified thresholds of 83% for sensitivity and 70% for specificity. Results. Eighty-two patients (13%) had acute TCMR grade I-III. In relation to the biopsy diagnosis of TCMR, the sensitivity of the urine test was 0.66 (95% confidence interval, 0.56-0.76) and the specificity 0.47 (95% confidence interval, 0.43-0.51), with an area under the curve (AUC) of 0.60. The different TCMR grades I-III were not reflected by the marker set, and borderline TCMR was not specifically detected. Secondary independent masked assessment of biopsies consented by 2 pathologists revealed an interobserver kappa value of 0.49 for diagnosing TCMR, compared with the local center's diagnosis. Using this consensus diagnosis, the AUC of the urine test was 0.63 (sensitivity 0.73, specificity 0.45). Post hoc optimization of the marker set improved the diagnostic performance in the study cohort (AUC 0.67) and in an independent patient cohort (AUC 0.69). Conclusions. This study illustrates the difficulty of proteomics-based diagnosis of TCMR and highlights the need for rigorous independent in-place validation and optimization of diagnostic biomarkers.
CRIS-Team WoS Importer:2022-04-29

Pharmacodynamic effect of mTOR inhibition-based immunosuppressive therapy on dendritic cell and natural killer cell subsets after renal transplantation - Weber, Sabine; Wei, Xinyi; Chen, Guangliang; Yankouskaya, Katharina; Yin, Decheng; Allabauer, Ida; Jobst-Schwan, Tilman; Wiesener, Michael; Schiffer, Mario; Dudziak, Diana; Lehmann, Christian; Wölfle, Joachim; et al. (Clinical and Experimental Immunology, 2025)
Background. mTOR inhibitor therapy is solely monitored via pharmacokinetics after kidney transplantation, which may not accurately reflect the effectiveness of PI3K-Akt-mTOR pathway blockade, potentially leading to inadequate or excessive immunosuppression. The pharmacodynamic effect of mTOR inhibition on natural killer (NK) cells and dendritic cell (DC) subsets after renal transplantation has not been investigated so far. Methods. Phosphoflow cytometry was employed in this cross-sectional study to evaluate the extent of mTOR inhibition in peripheral DC and NK cell subsets by assessing p70S6 kinase phosphorylation in kidney transplant recipients treated with mTOR inhibitors either in combination with calcineurin inhibitors (mTORi + CNI, n = 17) or mycophenolate sodium (mTORi + MPA, n = 9). The control group comprised nine end-stage renal disease patients undergoing dialysis therapy and 17 healthy volunteers. Results. mTOR inhibitor-based therapy significantly reduced p70S6K phosphorylation levels in CD3-CD56+ NK cells compared to healthy controls, while p70S6K phosphorylation among HLA-DR+ Lin- total DCs was not different. In comparison to mTORi + MPA therapy, renal transplant patients receiving mTORi + CNI treatment exhibited a stronger inhibition of p70S6K phosphorylation in HLA-DR+ Lin- total DCs, CD123+CD11c- plasmacytoid DCs, CD123-CD11c+ myeloid DCs, and CD16-CD56bright NK cells. However, the serum trough levels of mTORi showed no correlation with p70S6K phosphorylation levels in all investigated cell subsets. Conclusion. mTORi selectively suppressed p70S6K phosphorylation in specific DC and NK subtypes. Evaluating p70S6K phosphorylation through phosphoflow cytometry might serve as a clinically applicable method to comprehend immune cell subset-specific effects of mTOR inhibition, providing detailed pharmacodynamic insights for tailoring mTORi therapy on an individual basis.
CRIS-Team Scopus Importer:2025-05-30
Keywords: calcineurin inhibitors; dendritic cells; kidney transplantation; mTORi; NK cells; p70S6 kinase; phosphoflow cytometry

Pharmacodynamic Effect of mTOR Inhibition-based Immunosuppressive Therapy on T- and B-cell Subsets After Renal Transplantation - Wei, Xinyi; Weber, Sabine; Yin, Decheng; Allabauer, Ida; Jobst-Schwan, Tilman; Wiesener, Michael; Schiffer, Mario; Dudziak, Diana; Lehmann, Christian; Wölfle, Joachim; Hörning, Andre (Transplantation Direct, 2024)
Background. The mammalian target of rapamycin inhibitor (mTORi) therapy after kidney transplantation is solely monitored pharmacokinetically, not necessarily reflecting PI3K-Akt-mTOR pathway blockade efficacy leading to potential under- or overimmunosuppression. Methods. In this cross-sectional study, phosphoflow cytometry was used to determine the efficacy of mTOR inhibition in peripheral T- and B-lymphocyte subsets by assessing p70S6 kinase (p70S6K) phosphorylation in renal transplant recipients upon treatment with a combination of either mTORi and calcineurin inhibitors (n = 18), or mTORi with mycophenolic acid (n = 9). Nine dialysis patients with end-stage renal disease and 17 healthy age-matched volunteers served as controls. Results. mTORi treatment reduced p70S6K phosphorylation in CD4+, CD8+ T, and CD19+ B cells compared with healthy controls (HCs). Subpopulation analysis of CD4+ T cells and CD19+ B cells revealed a significant reduction of p70S6K phosphorylation in CD4+CD45RA−CD25− Th cells (P < 0.05), CD24hiCD38hi transitional B cells (P < 0.001), CD24+CD38− memory B cells (P < 0.001), and CD24intCD38int-naive B cells (P < 0.05) upon mTORi treatment, whereas CD4+CD45RA−CD25++CD127− regulatory T cells and CD24−CD38hi plasmablasts were not affected. Compared with mTORi + mycophenolic acid therapy, mTORi + calcineurin inhibitor treatment exhibited an even stronger inhibition of p70S6K phosphorylation in CD4+CD45RA−CD25− Th cells and CD8+ T cells. However, trough levels of mTORi did not correlate with p70S6K phosphorylation. Conclusions. mTORi selectively inhibited p70S6K phosphorylation in select lymphocyte subtypes. Assessing p70S6K phosphorylation by phosphoflow cytometry may serve as an approach to understand cell subset specific effects of mTORi providing detailed pharmacodynamic information for individualizing immunosuppression.
CRIS-Team Scopus Importer:2024-07-19

PI(3,4)P2-mediated cytokinetic abscission prevents early senescence and cataract formation - Gulluni, Federico; Prever, Lorenzo; Li, Huayi; Krafcikova, Petra; Corrado, Ilaria; Lo, Wen-Ting; Margaria, Jean Piero; Chen, Anlu; De Santis, Maria Chiara; Cnudde, Sophie J.; Fogerty, Joseph; Yuan, Alex; et al. (Science, 2021)
Cytokinetic membrane abscission is a spatially and temporally regulated process that requires ESCRT (endosomal sorting complexes required for transport)–dependent control of membrane remodeling at the midbody, a subcellular organelle that defines the cleavage site. Alteration of ESCRT function can lead to cataract, but the underlying mechanism and its relation to cytokinesis are unclear. We found a lens-specific cytokinetic process that required PI3K-C2a (phosphatidylinositol-4-phosphate 3-kinase catalytic subunit type 2a), its lipid product PI(3,4)P2 (phosphatidylinositol 3,4-bisphosphate), and the PI(3,4)P2–binding ESCRT-II subunit VPS36 (vacuolar protein-sorting-associated protein 36). Loss of each of these components led to impaired cytokinesis, triggering premature senescence in the lens of fish, mice, and humans. Thus, an evolutionarily conserved pathway underlies the cell type–specific control of cytokinesis that helps to prevent early onset cataract by protecting from senescence.
CRIS-Team Scopus Importer:2021-12-24

Preemptive Conversion to mTOR Inhibition to Prevent Primary Cytomegalovirus Infection in Kidney Transplantation with High-Risk Serostatus - Paulwitz, Jan; Vonbrunn, Laura; Heller, Katharina M.; Dieterle, Anne; Apel, Hendrik; Schiffer, Mario; Wiesener, Michael; Dienemann, Thomas (Transplantation Proceedings, 2025)
Background: Kidney transplantation (KTx) is the treatment of choice for patients with end-stage renal disease. Cytomegalovirus (CMV) infection remains a serious complication of KTx. The most vulnerable patients are naïve recipients (R-) transplanted from a CMV-seropositive donor (D+). Mammalian target of rapamycin inhibitors (mTOR-I) have been shown to have advantages over mycophenolate in terms of CMV infections. In this study, we addressed the effect of preemptive conversion to mTOR-I before ending prophylaxis with valganciclovir in high-risk patients with a D+/R- CMV serostatus. Methods: The study involved inclusion and analysis of all patients with D+/R- CMV serostatus before and after the protocol change with a conversion to mTOR-I at 6 months after KTx. The main study endpoints were primary CMV infection, maximal viral load, and hospitalization for CMV infection. Because prevention of primary CMV infections was the primary endpoint, we excluded breakthrough infections under prophylaxis. Results: The primary analysis included 44 patients in the control group and 39 patients in the mTOR group. The 2 groups did not have any significant differences in clinical characteristics, immunosuppressive treatment, transplant function, and rates of rejection. Between 6 and 12 months (when mTOR-I were established), the mTOR group showed a numerically lower incidence of CMV infections, as well as numerically fewer hospitalizations. No serious complications were observed with mTOR-I. Conclusion: Preemptive conversion from mycophenolate to mTOR-I may be helpful to prevent or attenuate primary infection in CMV high-risk kidney transplant recipients. Differences were not statistically significant. A larger study, ideally a prospective randomized trial, is needed to validate these findings.
CRIS-Team Scopus Importer:2025-05-23

Prenatal diagnosis of HNF1B-associated renal cysts: Is there a need to differentiate intragenic variants from 17q12 microdeletion syndrome? - Vasileiou, Georgia; Hoyer, Juliane; Thiel, Christian; Schaefer, Jan Thomas; Zapke, Maren; Krumbiegel, Mandy; Kraus, Cornelia; Zweier, Markus; Uebe, Steffen; Ekici, Arif Bülent; Schneider, Michael; Wiesener, Michael; et al. (Prenatal Diagnosis, 2019)
Objective 17q12 microdeletions containing HNF1B and intragenic variants within this gene are associated with variable developmental, endocrine, and renal anomalies, often already noted prenatally as hyperechogenic/cystic kidneys. Here, we describe prenatal and postnatal phenotypes of seven individuals with HNF1B aberrations and compare their clinical and genetic data to those of previous studies. Methods Prenatal sequencing and postnatal chromosomal microarray analysis were performed in seven individuals with renal and/or neurodevelopmental phenotypes. We evaluated HNF1B-related clinical features from 82 studies and reclassified 192 reported intragenic HNF1B variants. Results In a prenatal case, we identified a novel in-frame deletion p.(Gly239del) within the HNF1B DNA-binding domain, a mutational hot spot as demonstrated by spatial clustering analysis and high computational prediction scores. The six postnatally diagnosed individuals harbored 17q12 microdeletions. Literature screening revealed variable reporting of HNF1B-associated clinical traits. Overall, both mutation groups showed a high phenotypic heterogeneity. The reclassification of all previously reported intragenic HNF1B variants provided an up-to-date overview of the mutational spectrum. Conclusions We highlight the value of prenatal HNF1B screening in renal developmental diseases. Standardized clinical reporting and systematic classification of HNF1B variants are necessary for a more accurate risk quantification of prenatal and postnatal clinical features, improving genetic counseling and prenatal decision making.
CRIS-Team WoS Importer:2019-11-08

Prevalence of hereditary tubulointerstitial kidney diseases in the German Chronic Kidney Disease study - Popp, Bernt; Ekici, Arif Bülent; Knaup, Karl; Schneider, Karen; Uebe, Steffen; Park, Jonghun; Bafna, Vineet; Meiselbach, Heike; Eckardt, Kai-Uwe; Schiffer, Mario; Wiesmann da Silva Reis, André; Kraus, Cornelia; et al. (European Journal of Human Genetics, 2022)
Hereditary chronic kidney disease (CKD) appears to be more frequent than the clinical perception. Exome sequencing (ES) studies in CKD cohorts could identify pathogenic variants in similar to 10% of individuals. Tubulointerstitial kidney diseases, showing no typical clinical/histologic finding but tubulointerstitial fibrosis, are particularly difficult to diagnose. We used a targeted panel (29 genes) and MUC1-SNaPshot to sequence 271 DNAs, selected in defined disease entities and age cutoffs from 5217 individuals in the German Chronic Kidney Disease cohort. We identified 33 pathogenic variants. Of these 27 (81.8%) were in COL4A3/4/5, the largest group being 15 COL4A5 variants with nine unrelated individuals carrying c.1871G>A, p.(Gly624Asp). We found three cysteine variants in UMOD, a novel missense and a novel splice variant in HNF1B and the homoplastic MTTF variant m.616T>C. Copy-number analysis identified a heterozygous COL4A5 deletion, and a HNF1B duplication/deletion, respectively. Overall, pathogenic variants were present in 12.5% (34/271) and variants of unknown significance in 9.6% (26/271) of selected individuals. Bioinformatic predictions paired with gold standard diagnostics for MUC1 (SNaPshot) could not identify the typical cytosine duplication ("c.428dupC") in any individual, implying that ADTKD-MUC1 is rare. Our study shows that >10% of selected individuals carry disease-causing variants in genes partly associated with tubulointerstitial kidney diseases. COL4A3/4/5 genes constitute the largest fraction, implying they are regularly overlooked using clinical Alport syndrome criteria and displaying the existence of phenocopies. We identified variants easily missed by some ES pipelines. The clinical filtering criteria applied enriched for an underlying genetic disorder.
CRIS-Team WoS Importer:2022-09-23

Progressive Kidney Failure by Angiotensinogen Inactivation in the Germline - Wopperer, Florian; Olinger, Eric; Wiesener, Antje; Broeker, Katharina A.E.; Knaup, Karl; Schaefer, Jan Thomas; Galiano, Matthias; Schneider, Karen; Schiffer, Mario; Büttner-Herold, Maike; Reis, André; Schmieder, Roland; et al. (Hypertension, 2024)
BACKGROUND: Autosomal recessive renal tubular dysgenesis is a rare, usually fatal inherited disorder of the REN (renin)angiotensin system. Herein, we report an adolescent individual experiencing an unknown chronic kidney disease and aim to provide novel insights into disease mechanisms. METHODS: Exome sequencing for a gene panel associated with renal disease was performed. The REN-angiotensin system was assessed by comprehensive biochemical analysis in blood. REN expression was determined in primary tubular cells by quantitative polymerase chain reaction and in situ hybridization on kidney biopsy samples. Allele frequencies of heterozygous and biallelic deleterious variants were determined by analysis of the Genomics England 100,000 Genomes Project. RESULTS: The patient was delivered prematurely after oligohydramnios was detected during pregnancy. Postnatally, he recovered from third-degree acute kidney injury but developed chronic kidney disease stage G3b over time. Exome sequencing revealed a previously reported pathogenic homozygous missense variant, p.(Arg375Gln), in the AGT (angiotensinogen) gene. Blood AGT concentrations were low, but plasma REN concentration and gene expression in kidney biopsy, vascular, and tubular cells revealed strong upregulation of REN. Angiotensin II and aldosterone in blood were not abnormally elevated. CONCLUSIONS: Renal tubular dysgenesis may present as chronic kidney disease with a variable phenotype, necessitating broad genetic analysis for diagnosis. Functional analysis of the renin-angiotensin system in a patient with AGT mutation revealed novel insights regarding compensatory upregulation of REN in vascular and tubular cells of the kidney and in plasma in response to depletion of AGT substrate as a source of Ang II (similarly observed with hepatic AGT silencing for the treatment of hypertension).
CRIS-Team Scopus Importer:2024-07-26
Keywords: angiotensinogen; exome; mass spectrometry; mutation; renin-angiotensin system

Rabbit-ATG or basiliximab induction for rapid steroid withdrawal after renal transplantation (Harmony): an open-label, multicentre, randomised controlled trial - Thomusch, Oliver; Wiesener, Michael; Opgenoorth, Mirian; Pascher, Andreas; Woitas, Rainer Peter; Witzke, Oliver; Jaenigen, Bernd; Rentsch, Markus; Wolters, Heiner; Rath, Thomas; Cingöz, Tülay; Benck, Urs; et al. (The Lancet, 2016)
Standard practice for immunosuppressive therapy after renal transplantation is quadruple therapy using antibody induction, low-dose tacrolimus, mycophenolate mofetil, and corticosteroids. Long-term steroid intake significantly increases cardiovascular risk factors with negative effects on the outcome, especially post-transplantation diabetes associated with morbidity and mortality. In this trial, we examined the efficacy and safety parameters of rapid steroid withdrawal after induction therapy with either rabbit antithymocyte globulin (rabbit ATG) or basiliximab in immunologically low-risk patients during the first year after kidney transplantation.In this open-label, multicentre, randomised controlled trial, we randomly assigned renal transplant recipients in a 1:1:1 ratio to receive either basiliximab induction with low-dose tacrolimus, mycophenolate mofetil, and steroid maintenance therapy (arm A), rapid corticosteroid withdrawal on day 8 (arm B), or rapid corticosteroid withdrawal on day 8 after rabbit ATG (arm C). The study was done in 21 centres across Germany. Only participants aged between 18 and 75 years with a low immunological risk who were scheduled to receive a single-organ renal transplant from either a living donor or a deceased donor were considered for enrolment. Patients receiving a second renal transplant were eligible, provided that the first allograft was not lost due to acute rejection within the first year after transplantation. Donor and recipient had to be ABO compatible. Grafts with pre-transplant existing donor-specific human leukocyte antigen (HLA) antibodies were not eligible and the recipients had to have a panel-reactive antibody concentration of 30% or less. Pregnant women and nursing mothers were excluded from the study. The primary endpoint was the incidence of biopsy-proven acute rejection (BPAR) at 12 months. All analyses were done by intention-to-treat. This trial is registered with ClinicalTrials.gov, number NCT00724022.Between Aug 7, 2008, and Nov 30, 2013, 615 patients were randomly assigned to arm A (206), arm B (189), and arm C (192). BPAR rates were not reduced by rabbit ATG (9·9%) compared with either treatment arm A (11·2%) or B (10·6%; A versus C: p=0·75, B versus C p=0·87). As a secondary endpoint, rapid steroid withdrawal reduced post-transplantation diabetes in arm B to 24% and in arm C to 23% compared with 39% in control arm A (A versus B and C: p=0·0004). Patient survival (94·7% in arm A, 97·4% in arm B, and 96·9% in arm C) and censored graft survival (96·1% in arm A, 96·8% in arm B, and 95·8% in arm C) after 12 months were excellent and equivalent in all arms. Safety parameters such as infections or the incidence of post-transplantation malignancies did not differ between the study arms.Rabbit ATG did not show superiority over basiliximab induction for the prevention of BPAR after rapid steroid withdrawal within 1 year after renal transplantation. Nevertheless, rapid steroid withdrawal after induction therapy for patients with a low immunological risk profile can be achieved without loss of efficacy and is advantageous in regard to post-transplantation diabetes incidence.Investigator Initiated Trial; financial support by Astellas Pharma GmbH, Sanofi, and Roche Pharma A
EVALuna2:3935

Renal fibrosis is the common feature of autosomal dominant tubulointerstitial kidney diseases caused by mutations in mucin 1 or uromodulin - Ekici, Arif Bülent; Hackenbeck, Thomas; Moriniere, Vincent; Panness, Andrea; Büttner, Maike; Uebe, Steffen; Janka, Rolf Matthias; Wiesener, Antje; Hermann, Ingo; Grupp, Sina; Hornberger, Martin; Huber, Tobias B.; et al. (Kidney International, 2014)
For decades, ill-defined autosomal dominant renal diseases have been reported, which originate from tubular cells and lead to tubular atrophy and interstitial fibrosis. These diseases are clinically indistinguishable, but caused by mutations in at least four different genes: UMOD, HNF1B, REN, and, as recently described, MUC1. Affected family members show renal fibrosis in the biopsy and gradually declining renal function, with renal failure usually occurring between the third and sixth decade of life. Here we describe 10 families and define eligibility criteria to consider this type of inherited disease, as well as propose a practicable approach for diagnosis. In contrast to what the frequently used term 'Medullary Cystic Kidney Disease' implies, development of (medullary) cysts is neither an early nor a typical feature, as determined by MRI. In addition to Sanger and gene panel sequencing of the four genes, we established SNaPshot minisequencing for the predescribed cytosine duplication within a distinct repeat region of MUC1 causing a frameshift. A mutation was found in 7 of 9 families (3 in UMOD and 4 in MUC1), with one indeterminate (UMOD p.T62P). On the basis of clinical and pathological characteristics we propose the term 'Autosomal Dominant Tubulointerstitial Kidney Disease' as an improved terminology. This should enhance recognition and correct diagnosis of affected individuals, facilitate genetic counseling, and stimulate research into the underlying pathophysiology.
EVALuna2:3695

Renal tubular HIF-2α expression requires VHL inactivation and causes fibrosis and cysts - Schietke, Ruth E.; Hackenbeck, Thomas; Tran, Maxine; Guenther, Regina; Klanke, Bernd; Warnecke, Christina; Knaup, Karl X.; Shukla, Deepa; Rosenberger, Christian; Koesters, Robert; Bachmann, Sebastian; Betz, Peter; et al. (PLoS ONE, 2012)
The Hypoxia-inducible transcription Factor (HIF) represents an important adaptive mechanism under hypoxia, whereas sustained activation may also have deleterious effects. HIF activity is determined by the oxygen regulated α-subunits HIF-1α or HIF-2α. Both are regulated by oxygen dependent degradation, which is controlled by the tumor suppressor "von Hippel-Lindau" (VHL), the gatekeeper of renal tubular growth control. HIF appears to play a particular role for the kidney, where renal EPO production, organ preservation from ischemia-reperfusion injury and renal tumorigenesis are prominent examples. Whereas HIF-1α is inducible in physiological renal mouse, rat and human tubular epithelia, HIF-2α is never detected in these cells, in any species. In contrast, distinct early lesions of biallelic VHL inactivation in kidneys of the hereditary VHL syndrome show strong HIF-2α expression. Furthermore, knockout of VHL in the mouse tubular apparatus enables HIF-2α expression. Continuous transgenic expression of HIF-2α by the Ksp-Cadherin promotor leads to renal fibrosis and insufficiency, next to multiple renal cysts. In conclusion, VHL appears to specifically repress HIF-2α in renal epithelia. Unphysiological expression of HIF-2α in tubular epithelia has deleterious effects. Our data are compatible with dedifferentiation of renal epithelial cells by sustained HIF-2α expression. However, HIF-2α overexpression alone is insufficient to induce tumors. Thus, our data bear implications for renal tumorigenesis, epithelial differentiation and renal repair mechanisms. © 2012 Schietke et al.

Renal uptake of the antiapoptotic protein survivin is mediated by megalin at the apical membrane of the proximal tubule - Jobst-Schwan, Tilman; Knaup, Karl; Nielsen, Rikke; Hackenbeck, Thomas; Büttner-Herold, Maike; Lechler, Philipp; Kroening, Sven; Goppelt-Strübe, Margarete; Schlötzer-Schrehardt, Ursula; Fuernrohr, Barbara G.; Voll, Reinhard E.; Amann, Kerstin Ute; et al. (American Journal of Physiology-Renal Physiology, 2013)
The inhibitor of apoptosis protein survivin is a bifunctional molecule that regulates cellular division and survival. We have previously shown that survivin protein can be found at high concentrations in the adult kidney, particularly in the proximal tubules. Here, survivin is localized primarily at the apical membrane, a pattern that may indicate absorption of the protein. Several proteins in primary urine are internalized by megalin, an endocytosis receptor, which is in principle found in the same localization as survivin. Immunolabeling for survivin in different species confirmed survivin signal localizing to the apical membrane of the proximal tubule. Immunoelectron microscopy also showed apical localization of survivin in human kidneys. Furthermore, in polarized human primary tubular cells endogenous as well as external recombinant survivin is stored in the apical region of the cells. Costaining of survivin and megalin by immunohistochemistry and immunoelectron microscopy confirmed colocalization. Finally, by surface plasmon resonance we were able to demonstrate that survivin binds megalin and cubilin and that megalin knockout mice lose survivin through the urine. Survivin accumulates at the apical membrane of the renal tubule by reuptake, which is achieved by the endocytic receptor megalin, collaborating with cubilin. For this to occur, survivin will have to circulate in the blood and be filtered into the primary urine. It is not known at this stage what the functional role of tubular survivin is. However, a small number of experimental and clinical reports implicate that renal survivin is important for functional integrity of the kidney. © 2013 by the American Physiological Society.
Created from Fastlane, Scopus look-up
Keywords: Acute kidney injury; Apoptosis; Glomerular filtration; Lysosomes; Proteinuria

Single molecule real time sequencing in ADTKD-MUC1 allows complete assembly of the VNTR and exact positioning of causative mutations - Wenzel, Andrea; Altmueller, Janine; Ekici, Arif Bülent; Popp, Bernt; Stueber, Kurt; Thiele, Holger; Pannes, Alois; Staubach, Simon; Salido, Eduardo; Nuernberg, Peter; Reinhardt, Richard; Reis, André; et al. (Scientific Reports, 2018)
Recently, the Mucin-1 (MUC1) gene has been identified as a causal gene of autosomal dominant tubulointerstitial kidney disease (ADTKD). Most causative mutations are buried within a GC-rich 60 basepair variable number of tandem repeat (VNTR), which escapes identification by massive parallel sequencing methods due to the complexity of the VNTR. We established long read single molecule real time sequencing (SMRT) targeted to the MUC1-VNTR as an alternative strategy to the snapshot assay. Our approach allows complete VNTR assembly, thereby enabling the detection of all variants residing within the VNTR and simultaneous determination of VNTR length. We present high resolution data on the VNTR architecture for a cohort of snapshot positive (n = 9) and negative (n = 7) ADTKD families. By SMRT sequencing we could confirm the diagnosis in all previously tested cases, reconstruct both VNTR alleles and determine the exact position of the causative variant in eight of nine families. This study demonstrates that precise positioning of the causative mutation(s) and identification of other coding and noncoding sequence variants in ADTKD-MUC1 is feasible. SMRT sequencing could provide a powerful tool to uncover potential factors encoded within the VNTR that associate with intra- and interfamilial phenotype variability of MUC1 related kidney disease.
EVALuna2:34138

Suspected colonic cancer turns out to be disseminated tuberculosis in a kidney transplant recipient: A case report - Schmidt-Lauber, Christian; Jacobi, Johannes; Polifka, Iris; Hilgers, Karl Friedrich; Wiesener, Michael (Medicine, 2019)
Rationale: Active tuberculosis constitutes a relevant risk for kidney transplant recipients. In contrast to immunocompetent hosts, kidney transplant recipients often show atypical presentation and course of the disease impeding diagnosis. Especially extrapulmonary or disseminated infection is more frequent and can resemble malignant processes. However, reactivation of tuberculosis mostly develops within the early post-transplant course, whereas malignancies are predominantly long-term complications. We report a case of disseminated abdominal tuberculosis developing 10 years after kidney transplantation and review the underlying literature. Patient concerns and diagnoses: A 51-year-old lady presented with epigastric pain, diarrhea, weight loss and night sweats 10 years after deceased-donor kidney transplantation. An epigastric as well as multiple peritoneal masses were found suspicious of a cancer of unknown primary. Colonoscopy revealed a colon tumor with the biopsy showing no dysplasia but histiocytic and granulomatous infiltration with acid-fast bacilli. Mycobacterium tuberculosis was detected in the biopsy and stool and disseminated abdominal tuberculosi was diagnosed. Interventions and outcomes: With anti-tuberculosis therapy, the masses regressed, and all cultures became sterile, sparing graft function. Lessons: This case emphasizes how variable and unspecific the presentation of tuberculosis in kidney transplant recipients may be and that tuberculosis constitutes a relevant risk also in the long-term post-transplant course.
CRIS-Team Scopus Importer:2019-09-17
Keywords: abdominal masses; colon tumor; kidney transplantation; peritoneal carcinomatosis; tuberculosis

The lysyl oxidases LOX and LOXL2 are necessary and sufficient to repress E-cadherin in Hypoxia: Insights into cellular transformation processes mediated by HIF-1 - Schietke, Ruth; Warnecke, Christina; Wacker, Ingrid; Schödel, Johannes; Mole, David R.; Campean, Valentina; Amann, Kerstin Ute; Goppelt-Strübe, Margarete; Behrens, Jürgen; Eckardt, Kai-Uwe; Wiesener, Michael Sean (Journal of Biological Chemistry, 2010)
Hypoxia has been shown to promote tumor metastasis and lead to therapy resistance. Recent work has demonstrated that hypoxia represses E-cadherin expression, a hallmark of epithelial to mesenchymal transition, which is believed to amplify tumor aggressiveness. The molecular mechanism of E-cadherin repression is unknown, yet lysyl oxidases have been implicated to be involved. Gene expression of lysyl oxidase (LOX) and the related LOX-like 2 (LOXL2) is strongly induced by hypoxia. In addition to the previously demonstrated LOX, we characterize LOXL2 as a direct transcriptional target of HIF-1. We demonstrate that activation of lysyl oxidases is required and sufficient for hypoxic repression of E-cadherin, which mediates cellular transformation and takes effect in cellular invasion assays. Our data support a molecular pathway from hypoxia to cellular transformation. It includes up-regulation of HIF and subsequent transcriptional induction of LOX and LOXL2, which repress E-cadherin and induce epithelial to mesenchymal transition. Lysyl oxidases could be an attractive molecular target for cancers of epithelial origin, in particular because they are partly extracellular. © 2010 by The American Society for Biochemistry and Molecular Biology, Inc.
CRIS-Team Scopus Importer:2024-05-13

The renal cancer risk allele at 14q24.2 activates a novel hypoxia-inducible transcription factor-binding enhancer of DPF3 expression - Protze, Johanna; Naas, Stephanie; Krüger, René; Stöhr, Christine; Kraus, Andre; Grampp, Steffen; Schiffer, Mario; Hartmann, Arndt; Wullich, Bernd; Schödel, Johannes; Wiesener, Michael (Journal of Biological Chemistry, 2022)
Evolution of clear cell renal cell carcinoma is guided by dysregulation of hypoxia-inducible transcription factor (HIF) pathways following loss of the von Hippel-Lindau tumor suppressor protein. Renal cell carcinoma (RCC)-associated polymorphisms influence HIF–DNA interactions at enhancers of important oncogenes thereby modulating the risk of developing renal cancer. A strong signal of genome-wide association with RCC was determined for the single nucleotide polymorphism (SNP) rs4903064, located on chr14q.24.2 within an intron of DPF3, encoding for Double PHD Fingers 3, a member of chromatin remodeling complexes; however, it is unclear how the risk allele operates in renal cells. In this study, we used tissue specimens and primary renal cells from a large cohort of RCC patients to examine the function of this polymorphism. In clear cell renal cell carcinoma tissue, isolated tumor cells as well as in primary renal tubular cells, in which HIF was stabilized, we determined genotype-specific increases of DPF3 mRNA levels and identified that the risk SNP resides in an active enhancer region, creating a novel HIF-binding motif. We then confirmed allele-specific HIF binding to this locus using chromatin immunoprecipitation of HIF subunits. Consequentially, HIF-mediated DPF3 regulation was dependent on the presence of the risk allele. Finally, we show that DPF3 deletion in proximal tubular cells retarded cell growth, indicating potential roles for DPF3 in cell proliferation. Our analyses suggest that the HIF pathway differentially operates on a SNP-induced hypoxia-response element at 14q24.2, thereby affecting DPF3 expression, which increases the risk of developing renal cancer.
CRIS-Team Scopus Importer:2022-03-18

The tumour suppressor protein VHL targets hypoxia-inducible factors for oxygen-dependent proteolysis - Maxwell, Patrick H.; Wiesener, Michael Sean; Chang, Gin-Wen; Clifford, Steven C.; Vaux, Emma C.; Cockman, Matthew E.; Wykoff, Charles C.; Pugh, Christopher W.; Maher, Eamonn R.; Ratcliffe, Peter John (Nature, 1999)
Hypoxia-inducible factor-1 (HIF-1) has a key role in cellular responses to hypoxia, including the regulation of genes involved in energy metabolism, angiogenesis and apoptosis1,2,3,4. The α subunits of HIF are rapidly degraded by the proteasome under normal conditions, but are stabilized by hypoxia5. Cobaltous ions or iron chelators mimic hypoxia, indicating that the stimuli may interact through effects on a ferroprotein oxygen sensor6,7. Here we demonstrate a critical role for the von Hippel-Lindau (VHL) tumour suppressor gene product pVHL in HIF-1 regulation. In VHL-defective cells, HIF α-subunits are constitutively stabilized and HIF-1 is activated. Re-expression of pVHL restored oxygen-dependent instability. pVHL and HIF α-subunits co-immunoprecipitate, and pVHL is present in the hypoxic HIF-1 DNA-binding complex. In cells exposed to iron chelation or cobaltous ions, HIF-1 is dissociated from pVHL. These findings indicate that the interaction between HIF-1 and pVHL is iron dependent, and thatit is necessary for the oxygen-dependent degradation of HIF α-subunits. Thus, constitutive HIF-1 activation may underlie the angiogenic phenotype of VHL-associated tumours. The pVHL/HIF-1 interaction provides a new focus for understanding cellular oxygen sensing.<br

Tuberculous granulomatous interstitial nephritis in a renal allograft - Schmidt-Lauber, Christian; Büttner-Herold, Maike; Schiffer, Mario; Wiesener, Michael (Kidney International, 2019)
CRIS-Team Scopus Importer:2019-10-29